Wer kommt, wenn es knallt? Verfügbarkeit von Einsatzkräften im Bevölkerungsschutz - Berliner, Leon; Müller, Anna; Fertig, Julia; Follmann, Andreas; Wunderlich, Robert (Notfall und Rettungsmedizin, 2025)
Background: The frequency and complexity of crises and disasters are steadily increasing. In Germany, civil protection is organized federally and relies heavily on volunteer engagement. During crises, particularly in critical infrastructures (KRITIS), workload significantly increases. Objective: This study examines the availability of civilian emergency personnel during disasters, focusing especially on individuals with dual roles—such as those employed in KRITIS and volunteering in civil protection—and the impact of dual roles as well as professional and private obligations on operational readiness. Materials and methods: As part of a national online survey conducted between June and October 2024, volunteers from civil protection organizations were contacted. The questionnaire collected demographic data, professional occupation, civil protection engagement, qualifications, working hours, leave options, and availability during deployments. Results: A total of 3681 complete responses were included in the analysis (N = 3681). Of the respondents, 51.6% are employed in a KRITIS sector, and 20.5% hold more than one volunteer position. Among physicians, 32.7% are engaged in more than one volunteer role. In the event of a disaster, 30% of volunteers are always available, 65% are only partially available, and 5% are not available at all. The main reason for unavailability is professional obligations (57.4%), particularly for those employed in KRITIS sectors and for physicians who report a high workload of 49 h per week. Conclusion: The results show that the availability of civilian emergency personnel during disasters is significantly limited by professional and private obligations as well as dual roles. In Germany, only about 671,500 out of 1.7 million (60.5%) people active in disaster management are readily available as volunteers. This issue is particularly acute for those employed in KRITIS sectors and for physicians. Low leave rates and demographic changes further exacerbate the issue. Targeted measures to reduce workload and attract new volunteers are necessary to strengthen the resilience of civil protection.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Civil defense; Critical infrastructure; Disaster medicine; Equal treatment of aid workers; Multiple use of rescue workers